2018
DOI: 10.1038/s41467-018-06485-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical cancer genomic profiling by three-platform sequencing of whole genome, whole exome and transcriptome

Abstract: To evaluate the potential of an integrated clinical test to detect diverse classes of somatic and germline mutations relevant to pediatric oncology, we performed three-platform whole-genome (WGS), whole exome (WES) and transcriptome (RNA-Seq) sequencing of tumors and normal tissue from 78 pediatric cancer patients in a CLIA-certified, CAP-accredited laboratory. Our analysis pipeline achieves high accuracy by cross-validating variants between sequencing types, thereby removing the need for confirmatory testing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
146
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 163 publications
(161 citation statements)
references
References 63 publications
(60 reference statements)
7
146
0
Order By: Relevance
“…Previously, we have shown that this approach achieved a positive predictive rate of 98.8% and a sensitivity of 94.3% for exonic indels, assuring the quality of the training set (Rusch et al, 2018). A possible limitation of the training set is that indels in the set were predominantly small indels with the maximum length being 23-nt.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Previously, we have shown that this approach achieved a positive predictive rate of 98.8% and a sensitivity of 94.3% for exonic indels, assuring the quality of the training set (Rusch et al, 2018). A possible limitation of the training set is that indels in the set were predominantly small indels with the maximum length being 23-nt.…”
Section: Discussionmentioning
confidence: 77%
“…In our initial assessment, nearly one third of RNA-Seq indels supported by WES were not validated by further investigations, suggesting that they were PCR artifacts common to both platforms. To construct a high-quality training set, we employed three-platform clinical sequencing of WGS, WES and RNA-Seq with WGS data generated from a PCR-free library protocol (Rusch et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WES and RNAseq were performed on the samples at the McGill University and Genome Quebec Innovation Center, according to current standards in precision oncology [55]. Sequencing was done using an Illumina HiSeq 2500 using the 'rapid-run' mode with 100 bp paired-end reads.…”
Section: Wes and Rnaseq Data Generationmentioning
confidence: 99%